The Role of Psychological Capital as Mediating the Effect of Job Insecurity on Job Satisfaction: An Investigation at the Banda Aceh - Ibrahim, Mahdani; Karollah, Banta; Vilzati,; Amir, Fakhrurrazi (International Journal of Social and Administrative Sciences, 2019)
This study aims to analyze the role of psychological capital in bridging the relationship between job insecurity and job satisfaction. It also aims to know the effect of job insecurity on job satisfaction. Contract workers at the "Meuraxa" General Hospital in Banda Aceh were the unit of analysis in this study, because we considered them to be very vulnerable to work insecurity related to termination of employment, as many as 112 contract workers we took as research samples. Primary data were obtained by distributing questionnaires to contract workers using random sampling techniques. Data were analyzed using Hierarchical Linear Modeling (HLM). The results of our analysis found that psychological capital plays an important role in bridging the relationship between job security and job satisfaction. The analysis also found a direct effect between job insecurity and job satisfaction. We conclude that psychological capital is a very important variable when job insecurity wants to increase job satisfaction.